Short-term outcomes after pancreatoduodenectomy in octogenarians: multicentre case–control study. Issue 1 (9th November 2021) - Attard, Joseph A; Al-Sarireh, Bilal; Bhogal, Ricky Harminder; Farrugia, Alexia; Fusai, Giuseppe; Harper, Simon; Hidalgo-Salinas, Camila; Jah, Asif; Marangoni, Gabriele; Mortimer, Matthew; Pizanias, Michail; Prachialias, Andreas; et al.
Abstract: Background: Pancreatoduodenectomy (PD) is frequently the surgical treatment indicated for a number of pathologies. Elderly patients may be denied surgery because of concerns over poor perioperative outcomes. The aim of this study was to evaluate postoperative clinical outcomes and provide evidence on current UK practice in the elderly population after PD. Methods: This was a multicentre retrospective case–control study of octogenarians undergoing PD between January 2008 and December 2017, matched with younger controls from seven specialist centres in the UK. The primary endpoint was 90-day mortality. Secondary endpoints were index admission mortality, postoperative complications, and 30-day readmission rates. Results: In total, 235 octogenarians (median age 81 (range 80–90) years) and 235 controls (age 67 (31–79) years) were included in the study. Eastern Cooperative Oncology Group performance status (median 0 (range 0–3) versus 0 (0–2); P  = 0.010) and Charlson Co-morbidity Index score (7 (6–11) versus 5 (2–9); P  = 0.001) were higher for octogenarians than controls. Postoperative complication and 30-day readmission rates were comparable. The 90-day mortality rate was higher among octogenarians (9 versus 3 per cent; P  = 0.030). Index admission mortality rates were comparable (4 versus 2 per cent; P  = 0.160), indicating that the difference in mortality was related to deaths after hospital discharge. Despite the higher 90-day mortality rate in the octogenarian population, multivariable Cox regression analysis did not identify age as an independent predictor of postoperative mortality. Conclusion: Despite careful patient selection and comparable index admission mortality, 90-day and, particularly, out-of-hospital mortality rates were higher in octogenarians. Abstract : Octogenarians may be denied pancreatoduodenectomy owing to concerns over poor perioperative outcomes. This multicentre retrospective case–control study concluded that, despite careful patient selection and comparable index admission mortality, 90-day and, particularly, out-of-hospital mortality rates were higher in octogenarians. Future studies should focus on measures to reduce this risk.